PENERAPAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI UNTUK MENINGKATKAN MINAT BELAJAR IPAS DI SD NEGERI 178 / IV KOTA JAMBI - Rahmawati, Dian; Atri Widowati; Indryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The use of animated video-based learning media can be an interesting alternative for teaching science material. Animated videos explain abstract scientific concepts in a visual and interesting way, and stimulate students' curiosity, so that learning becomes more interactive and fun. This research uses the Classroom Action Research (PTK) method with the research subjects being class V students at SD Negeri 178/IV Jambi City. The research procedure follows Suharsimi Arikunto's PTK model which consists of four stages, namely planning, acting, observation and reflection. The data in this research was collected through observation and documentation methods. The research results showed that the achievement of students' interest in learning at SDN 178/IV Jambi City increased from 56.92% in cycle I to 80.15% in cycle II, with an average increase of 68.53%. This increase can be seen in every indicator of learning interest: concentration of attention and thoughts on learning increased from 60.38% in cycle I to 85.38% in cycle II; willingness to learn from 53.46% in cycle I to 79.61% in cycle II; willingness to actively learn from 57.30% in cycle I to 80.00% in cycle II; and efforts to realize the desire to learn from 55.77% in cycle I to 76.53% in cycle II. This increase in interest in learning is caused by improvements made by teachers in the learning process, from the introductory to the closing stages, as well as the use of animated video media that is attractive to students.